2021
DOI: 10.3390/ijerph19010050
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Wellbeing, Worry, and Resilience-Based Coping during COVID-19 in Relation to Sleep Quality

Abstract: The current study evaluated the impact of psychological wellbeing on sleep quality during the onset of the COVID-19 pandemic. A novel empirical model tested variables that mediate and moderate this impact. First, a relationship was established between psychological wellbeing during the COVID-19 pandemic and sleep quality. Second, resilience-based coping associated with the COVID-19 pandemic was tested as a mediator of the impact of psychological wellbeing on sleep quality. Third, dispositional rumination, mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…With respect to the adopted methodology, we exclusively used self-report standardized questionnaires in order to reach a wide sample size easily, but more in-depth information about sleep habits could have been obtained with an extensive multi-method assessment using idiographic sleep diaries and objective measures, such as actigraphy. Finally, relevant data concerning other sleep disorders (e.g., obstructive sleep apnea, circadian rhythm disorders, and nightmares); health-relevant behaviors, such as substance misuse and the use of electronic devices; and specific psychological variables, such as resilience and coping, have not been gathered in our study, despite their role in the relationship between sleep and well-being, which is likely to be significant [ 24 , 72 , 73 , 74 ]. Additionally, no information was collected about contextual and individual factors related to the COVID-19 pandemic (e.g., exposure to contagion/infection, fear of contagion, and feelings of loneliness and isolation), and thus precise inferences about the possible impact of the subjective experience of the pandemic situation on the reported findings cannot be made.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the adopted methodology, we exclusively used self-report standardized questionnaires in order to reach a wide sample size easily, but more in-depth information about sleep habits could have been obtained with an extensive multi-method assessment using idiographic sleep diaries and objective measures, such as actigraphy. Finally, relevant data concerning other sleep disorders (e.g., obstructive sleep apnea, circadian rhythm disorders, and nightmares); health-relevant behaviors, such as substance misuse and the use of electronic devices; and specific psychological variables, such as resilience and coping, have not been gathered in our study, despite their role in the relationship between sleep and well-being, which is likely to be significant [ 24 , 72 , 73 , 74 ]. Additionally, no information was collected about contextual and individual factors related to the COVID-19 pandemic (e.g., exposure to contagion/infection, fear of contagion, and feelings of loneliness and isolation), and thus precise inferences about the possible impact of the subjective experience of the pandemic situation on the reported findings cannot be made.…”
Section: Discussionmentioning
confidence: 99%
“…Tousignant OH et al [32] evaluated how the psychological state of a person affected how well they slept during the COVID-19 epidemic in the United States. Results showed that dealing with the COVID-19 pandemic had an impact on psychological health and decreased sleep quality.…”
Section: Reviewmentioning
confidence: 99%
“…Crawley (2020) [20] , Nisticò V(2021) [29] , Kerr ML(2021) [33], Sarangi A(2021) [38] Depression, sadness, affects emotional capacity Panchal N(2021) [9] , Golechha(2020) [17] , Tousignant OH(2021) [32] , Wright K(2020) [37], Sarangi A(2021) [38] Disturb sleep cycle, diet, alcohol and addictive abuse Giuntella(2021) [11] Physical activity hampered;…”
Section: Individual Observation/outcomementioning
confidence: 99%
“…The adaptive function of dreaming, and whether dreaming is functional at all, continues to be debated among researchers (Hobson, 2009; Malinowski & Horton, 2015; Montangero & Cavallero, 2015). It is established that good or adaptive sleep is related to a myriad of positive health variables (Leary et al, 2020; Luyster et al, 2012; Peach et al, 2016; Tousignant et al, 2021). Good sleep is marked by intact and uninterrupted cyclic periods of rapid eye movement (REM) with concurrent periods of dreaming (Aserinsky & Kleitman, 1953; Kostopoulos, 2012).…”
Section: Dreams and Emotional Integrationmentioning
confidence: 99%